PENGEMBANGAN PEMBELAJARAN BERBASIS INKUIRI QUR'ANI - Darwis Hude; Akhmad Shunhaji; Mansur (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2022)
This study aims to determine inquiry-based learning in the Qur'an, as well as its implications in the development of learning. Inquiry-based learning is one of the student-centered learning strategies influenced by the constructivism philosophy, which aims to produce competency standards for graduates who are able to think critically, creatively, communicatively, and collaboratively, as a form of life skills that enable individuals to deal effectively with the demands and challenges of everyday life. In general, inquiry-based learning cues can be found in the Qur'an in inquisitive verses that begin with adawât al-istifhâm, either in the form of harf al-istifhâm (particle of interrogation) or in the form of ism al-istifhâm (interrogative noun). And in particular, it can be found in a series of verses of the Qur'an in Surah al-Thur/52: 29-43. which explains the invitation to think by combining empiricism and rationalism, or the scientific method. This invitation is addressed to the Meccan polytheists who accuse (hypothesize) the Prophet Muhammad as a shaman, madman, poet, author of the Qur'an. Inquiry-based learning cues can also be found in a series of verses in Surah al-Anbiya'/21: 51-67, which tells about the method used by the prophet Ibrahim a.s in teaching monotheism to his people. As well as in the series of verses of the Qur'an in Surah al-An'am/6: 75-79, which describes the investigation of the prophet Ibrahim a.s into the nature of God